Targeting Enterotoxins: Advancing Vaccine Development for Enterotoxigenic Escherichia coli ETEC - Josune Salvador-Erro; Yadira Pastor; Carlos Gamazo (Toxins)
Enterotoxigenic Escherichia coli (ETEC) is a major cause of diarrheal disease worldwide, particularly in children in low- and middle-income countries. Its ability to rapidly colonize the intestinal tract through diverse colonization factors and toxins underpins its significant public health impact. Despite extensive research and several vaccine candidates reaching clinical trials, no licensed vaccine exists for ETEC. This review explores the temporal and spatial coordination of ETEC virulence factors, focusing on the interplay between adherence mechanisms and toxin production as critical targets for therapeutic intervention. Advancements in molecular biology and host–pathogen interaction studies have uncovered species-specific variations and cross-reactivity between human and animal strains. In particular, the heat-labile (LT) and heat-stable (ST) toxins have provided crucial insights into molecular mechanisms and intestinal disruption. Additional exotoxins, such as EAST-1 and hemolysins, further highlight the multifactorial nature of ETEC pathogenicity. Innovative vaccine strategies, including multiepitope fusion antigens (MEFAs), mRNA-based approaches, and glycoconjugates, aim to enhance broad-spectrum immunity. Novel delivery methods, like intradermal immunization, show promise in eliciting robust immune responses. Successful vaccination against ETEC will offer an effective and affordable solution with the potential to greatly reduce mortality and prevent stunting, representing a highly impactful and cost-efficient solution to a critical global health challenge.